2014
DOI: 10.1021/ja5070137
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Alcohol Oxidation Mediated by Copper(II) and Nitroxyl Radicals

Abstract: 2,2′-Bipyridine-ligated copper complexes, in combination with TEMPO (2,2,6,6-tetramethylpiperidine-N-oxyl), are highly effective catalysts for aerobic alcohol oxidation. Considerable uncertainty and debate exist over the mechanism of alcohol oxidation mediated by CuII and TEMPO. Here, we report experimental and density functional theory (DFT) computational studies that distinguish among numerous previously proposed mechanistic pathways. Oxidation of various classes of radical-probe substrates shows that long-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
156
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 66 publications
(68 reference statements)
9
156
0
2
Order By: Relevance
“…These conditions have been shown to involve the nitroxides alternating between these two oxidation states, and between a copper bound and a free state 54 . Oxidation of benzyl alcohol using nitroxides 25b, 32 and 35 is complete within 1-2 h at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions have been shown to involve the nitroxides alternating between these two oxidation states, and between a copper bound and a free state 54 . Oxidation of benzyl alcohol using nitroxides 25b, 32 and 35 is complete within 1-2 h at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Sheldon et al found the accelerating effect of 2,2'-bipyridine (bpy) ligands on the Cu(II) catalytic system, [6] Koskinen et al optimized the type and amount of base with Cu(II), [7] and Stahl et al performed scope and limitation studies as well as kinetic and mechanistic investigations demonstrating the importance of Cu(I) salts and N-methyl-A C H T U N G T R E N N U N G imidazole (NMI) as base. [8][9][10][11] The applicability of the system has been expanded to prepare nitriles from aldehydes or alcohols using aqueous ammonia [12] or to oxidize amine [13] and amino alcohols [14] into imines and amino carbonyl compounds, respectively.…”
mentioning
confidence: 99%
“…It was reported by Stahl et al that the reaction rate is limited by aerobic oxidation of Cu(I). [11] One way this issue can be addressed is to operate at a higher oxygen pressure and this was recently reported by Stahl et al in a continuous flow reactor. [15] However, even if near quantitative formation of benzaldehyde from benzyl alcohol was obtained with a residence time of 5 min with 35 bar of diluted oxygen source (9% O 2 in N 2 ) at 100 8C, these experimental conditions (diluted O 2 and elevated temperature) might not be optimum for the following reasons.…”
mentioning
confidence: 99%
See 2 more Smart Citations